2019
DOI: 10.1111/petr.13348
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of sleep quality and patient‐reported outcomes in pediatric solid organ transplant candidates

Abstract: The current cross‐sectional, single‐center study aimed to examine sleep quality in a sample of adolescents awaiting solid organ transplantation and to explore associations between sleep quality and both health‐related quality of life and barriers to adherence. Thirty adolescents between the ages of 12 and 18 years (M age = 15.26, SD = 1.89) who were awaiting transplantation participated in this study. Participants completed measures of sleep quality, health‐related quality of life, and barriers to adherence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Overall, adolescent transplant recipients would likely benefit from psychoeducation about sleep hygiene, anticipatory guidance about how the transition to young adulthood can impact sleep, information about the potential sleep‐related side effects of their medication regimen, and ongoing clinical assessment of the contributors to sleep‐related symptomology. Further, given the link between sleep difficulties and barriers related to self‐management in adolescent patients awaiting transplantation, healthcare providers may gain valuable clinical insight by evaluating if and how sleep difficulties are negatively impacting adherence and self‐management in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, adolescent transplant recipients would likely benefit from psychoeducation about sleep hygiene, anticipatory guidance about how the transition to young adulthood can impact sleep, information about the potential sleep‐related side effects of their medication regimen, and ongoing clinical assessment of the contributors to sleep‐related symptomology. Further, given the link between sleep difficulties and barriers related to self‐management in adolescent patients awaiting transplantation, healthcare providers may gain valuable clinical insight by evaluating if and how sleep difficulties are negatively impacting adherence and self‐management in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in social and cultural norms, such as increased technology/social media use or increased homework demands after school, are likely responsible, at least in part, for the steady decline in children's total sleep duration over the past few decades . Comorbid sleep difficulties are even more prevalent among youth with special medical needs, with approximately 25% of liver transplant pediatric patients exhibiting clinically significant sleep problems . From a cumulative risk perspective, the confluence of general vulnerabilities for poor sleep among teens, along with medical and illness management factors salient to pediatric/transplant populations (eg, medication timing, immunosuppressive therapy, weight‐related factors, suboptimal sleep hygiene, mood disturbances, and comorbid diseases affecting sleep such diabetes or sleep disorders) is likely responsible for the higher rates of sleep difficulties observed among liver transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…To emphasize the additional impact of SDB on CV complications, studies confirmed twice as high estimated 10‐year stroke and coronary heart disease risk in RTx patients with SDB compared to those without SDB . Furthermore, poor sleep quality as a consequence is a possible barrier to medication regimen adherence . The beneficial effect of RTx on the severity of SDB remains controversial, and two out of three longitudinal studies reported no significant resolution of SDB after transplantation in adults …”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, poor sleep quality as a consequence is a possible barrier to medication regimen adherence. 13 The beneficial effect of RTx on the severity of SDB remains controversial, and two out of three longitudinal studies reported no significant resolution of SDB after transplantation in adults. 14,15 Although studies carried out in the adult setting advocate for the high prevalence and the clinical importance of SDB in renal transplant patients, the condition in pediatric population has not been well described.…”
mentioning
confidence: 99%
See 1 more Smart Citation